Penerapan Early Warning System untuk Meningkatkan Pengetahuan Karyawan dalam Pengendalian Hama Perkebunan Kelapa Sawit - Uli Abshor; Wanda Russianzi; Edi Wiraguna (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
This study aims to enhance the knowledge and skills of oil palm plantation workers at PT Kencana Sawit Indonesia in controlling pests through the application of the Early Warning Sistem (EWS). Based on findings from a Focus Group Discussion (FGD), four major challenges in pest control were identified: limited employee knowledge, inefficient task distribution, challenging topography, and delayed responses to pest outbreaks. An outreach program was conducted involving educational sessions supported by pre-test and post-test assessments. The results revealed a significant improvement in employee knowledge, with the average score increasing from 37% to 83%. Furthermore, participant satisfaction with the outreach activities reached 86.50%, as measured by a Likert scale survey. These results confirm that the EWS-based extension program successfully addressed critical knowledge gaps, fostered motivation among employees, and improved the overall efficiency of pest management practices. As a result, this initiative is expected to support more effective pest control and positively impact plantation productivity.